D614G mutation eventuates in all VOI and VOC in SARS-CoV-2: Is it part of the positive selection pioneered by Darwin? - Chiranjib Chakraborty; Abinit Saha; Ashish Ranjan Sharma; Manojit Bhattacharya; Sang-Soo Lee; Govindasamy Agoramoorthy (Elsevier, 2021)
Recently, several emerging variants of SARS-CoV-2 have originated from the Wuhan strain and spread throughout the globe within one and a half years. One mutation, D614G, is very prominent in all VOI and VOC in SARS-CoV-2. This mutation might help to increase the viral fitness in all emerging variants where the mutation is present. With the help of this mutation (D614G), the SARS-CoV-2 variants have gained viral fitness to enhance viral replication and increase transmission. This paper attempts to answer the question of whether the mutation (D614G) occurs due to positive selection or not.